Innovation Ecosystem Finance and Social Resilience in Central-Eastern Europe: A Bucharest Nine Perspective - Tokar, Volodymyr; Tyshchenko, Dmytro; Mishchenko, Anna; Franchuk, Tamara; Tipanov, Vladyslav (International Journal of Economics and Financial Issues, 2025)
This article explores the relationship between innovation ecosystem finance and social resilience in Central-Eastern Europe, focusing on the Bucharest Nine (B9) countries. The scientific problem addressed is the limited integration of financial innovation metrics into resilience assessments, particularly in post-socialist EU states. The study aims to evaluate how R&D investment influences national capacities to adapt to and recover from systemic crises. A mixed-methods approach is employed, combining quantitative analysis of financial indicators – R&D expenditure per capita, per employed person, and per R&D personnel – with a newly constructed Integral Social Resilience Index based on economic, political, social, and ecological dimensions. Data were sourced from Eurostat, the World Bank, and other reputable institutions. The findings reveal significant disparities within the B9: Estonia and Czechia lead in both innovation finance and resilience, while Romania and Bulgaria lag behind. The results demonstrate that high R&D investment aligns with stronger societal resilience, though institutional and governance factors mediate this relationship. Limitations include reliance on available quantitative data, lack of qualitative governance indicators, and limited generalizability beyond the B9. These constraints may be addressed through future multi-scalar and longitudinal studies. The study offers practical insights for policymakers aiming to align innovation finance with resilience-building and contributes a novel framework linking financial ecosystems to adaptive capacities.